GE_GERICHTE P/24163/2022 vom 13. November 2023 - GE Cour de justice (2023)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;INFRACTIONS CONTRE L'INTÉGRITÉ SEXUELLE;ABUS DE LA DÉTRESSE;SOUPÇON | CPP.310; CP.193; CP.189